Self-Regulated Learning, Growth Mindset and Students’ Grit in Career Preparation - Amelia Ajrina; Shahnaz Safitri (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
As a result of the closure of several workplaces and jobs during Covid-19 pandemic, many undergraduate students feel anxious and worried about the career prospects they want to pursue in the future. In this case, grit is needed by them so that they could be able to study diligently to prepare their goals. Furthermore, students' growth mindset and beliefs about their abilities contribute to grit. However, there is self-regulated learning (SRL) which plays a role in strengthening the relationship between growth mindset and grit in Covid-19 pandemic. This study investigated the mediating effect that self-regulated learning has on growth mindset and grit. This study is quantitative research using three questionnaires, i.e., Grit Short Scale (8 items, α=0.747); Theory of Intelligence Scale (4 items, α=0.846); and Motivated Strategies for Learning Questionnaire (44 items, α=0.918). The participants of this study were 207 undergraduate students from all over Indonesia. The analytical technique used in this study was Process Hayes in SPSS version 26.0. The result revealed that the growth mindset can increase student’s grit in career preparation during the Covid-19 pandemic and it is partially mediated by self-regulated learning. Furthermore, mediation emphasizes the relationship between growth mindset and grit. This research has practical implications for educational institutions, counsellors, and psychologists in career developmental centres to increase students’ grit by using a growth mindset and SRL as basis for intervention.Akibat adanya penutupan beberapa lapangan pekerjaan di masa pandemi Covid-19, tidak sedikit mahasiswa yang merasa cemas dan khawatir terhadap prospek karier yang ingin dijalaninya ke depan. Dalam hal ini, kegigihan diperlukan mahasiswa untuk untuk dapat tekun belajar dalam rangka mempersiapkankarier dan cita-citanya. Growth mindset yang dimiliki mahasiswa terhadap kemampuannya berkontribusi terhadap kegigihan. Namun demikian, terdapat peran self-regulated learning (SRL) yang menguatkan hubungan antara growth mindset dan kegigihan. Penelitian ini bertujuan untuk mengetahui efek mediasi yang dimiliki oleh SRL terhadap hubungan antara growth mindset dan kegigihan mahasiswa dalam persiapan karier di masa pandemi Covid-19. Penelitian menggunakan metode kuantitatif dengan menggunakan tiga kuesioner yaitu Grit Short Scale (8 item, α=0.747); Theory of Intelligence Scale (4 item, α=0.846); dan Motivated Strategies for Learning Questionnaire (44 item, α=0.918). Partisipan dari penelitian ini berjumlah 207 mahasiswa D3/D4/S1 dari seluruh Indonesia. Untuk menguji peran mediasi, digunakan teknik analisis menggunakan Micro Process Hayes pada SPSS versi 26.0. Hasil dari penelitian ini menunjukkan bahwa growth mindset dapat meningkatkan kegigihan mahasiswa dalam mempersiapkan karier di masa pandemi Covid-19 dan dimediasi secara parsial oleh regulasi dalam belajar. Lebih lanjut, mediasi yang dilakukan memiliki kontribusi untuk memperkuat hubungan antara growth mindset dengan kegigihan. Penelitian ini memiliki implikasi praktis yang dapat dilakukan lembaga pendidikan, konselor maupun psikolog yang praktik di klinik mahasiswa (career developmental center) untuk meningkatkan kegigihan mahasiswa dengan menggunakan growth mindset dan SRL sebagai landasan intervensi.